Effectiveness of a Positive Deviance–Based Educational Intervention on Children’s Self-Esteem for Bullying Prevention: A Quasi-Experimental Study - Wahyuni, Retno; Marliani, Marliani; Lusiatun, Lusiatun; Japar, Abdul; Pangaribuan, Ingka Kristina; Manurung, Herna Rinayanti; Adethia, Kismiasih; Fathahilah, Bunga Dwi; Sinaga, Intan Putri; Dalimunthe, Juwita Rantika (Journal of Applied Nursing and Health, 2026)
Background: Bullying is a critical school issue rooted in low self-esteem, which serves as a major vulnerability factor for children. This study aims to analyze the role of Positive Deviance (PD) education in improving children’s self-esteem as a bullying prevention strategy. Methods: A quantitative quasi-experimental pretest–posttest control group design was employed. The population consisted of grade VI students at SD Negeri 101893 Bangun Rejo, with a total sample of 58 students, divided into an experimental (n=29) and a control (n=29) group. Sampling involved identifying "positive deviants"—children who successfully overcame bullying risks—to develop the PD education module. Variables measured included knowledge, self-esteem (SE), and Positive Deviance Bullying behavior (PB) as dependent variables, collected via validated instruments. Ethical clearance was ensured throughout the procedure, and data were analyzed using Paired and Independent t-tests. Results: Most respondents were aged 11–12 years, and the experimental group had a higher proportion of females (65.5%). The experimental group showed significant improvements in knowledge (p=0.0001), self-esteem (p=0.043), and behavior (p=0.034). Independent t-test results confirmed significant differences between the experimental and control groups for knowledge (p=0.013), self-esteem (p=0.037), and behavior (p=0.024), indicating the intervention's effectiveness. Conclusion: Positive Deviance education effectively enhances children’s self-esteem, providing a vital psychological foundation for bullying prevention. It is recommended that future programs adopt a whole-school approach involving teachers and parents to support long-term behavioral change and sustainability.